Influence of female hormones on fascia elasticity: An elastography study. Issue 7 (25th July 2019) - Vita, Martin; Sedlackova, Zuzana; Herman, Miroslav; Furst, Tomas; Smekal, David; Cech, Zdenek
Abstract : The aim of this study was to examine the influence of hormonal changes during the menstrual cycle on deep fasciae. A total of 29 women, 17 users, and 12 nonusers of hormonal contraceptives were examined clinically and by ultrasound, including shear wave elastography, at two phases of the menstrual cycle. The thickness and elasticity of the fascia lata, thoracolumbar fascia, and plantar fascia were measured, compared between hormonal contraceptive users and nonusers, and correlated with clinical data. There were statistically significant differences between users and nonusers of hormonal contraceptives: the thoracolumbar fascia was thicker in nonusers ( P = 0.011), and nonusers had higher maximal and mean stiffnesses of the fascia lata ( P = 0.01 and 0.0095, respectively). Generally, nonusers had a higher body mass index (BMI). The elasticity of the thoracolumbar and the plantar fasciae did not differ significantly between the groups. We found no correlation between thickness and elasticity in the fasciae. There were no statistically significant differences in hypermobility, cephalgia, or dysmenorrhea between users and nonusers of hormonal contraceptives. The results of this pilot study suggest that deep fasciae can be evaluated by shear wave elastography. Nonusers of contraceptives had greater stiffness of the fascia lata and higher BMI. Clin. Anat. 32:941–947, 2019. © 2019 Wiley Periodicals, Inc.